IMMUNOLOGICAL REACTIVITY, LIPID PEROXIDATION AND ANTIOXIDANT ACTIVITY UNDER STRESS (LITERARY REVIEW) - Hamidova Saodat Khikmatovna (Scholar Express Journals, 2023)
According to Selye, stress is a stress reaction that occurs as a non-specific response of the body to the action of extreme unfavorable factors - stressors. By its biological nature, stress has an adaptive orientation and activates protective mechanisms to prevent the pathogenic effect of adverse environmental factors on the body.
Keywords: immune response; thyroid; Selye stress.